The Number of Grains, The Number of Seeds in the Grains, The Mass and the Weight of 1000 Grains in the Peanut Plant - Mahmudov Utkir Haydarovich; Khalikov Bakhodir (International Journal on Economics, Finance and Sustainable Development, 2021)
This article describes the results obtained from the variants in which the number of legumes per bush is lower (180 and 230 thousand), with an increase in the planting norms of peanuts (280 and 330 thousand) in the light gray soils of Kashkadarya region.